1989
DOI: 10.1128/jvi.63.1.403-410.1989
|View full text |Cite
|
Sign up to set email alerts
|

Processing of the gp55-116 envelope glycoprotein complex (gB) of human cytomegalovirus

Abstract: The processing pathway of the major envelope glycoprotein complex, gp55-116 (gB), of human cytomegalovirus was studied using inhibitors of glycosylation and endoglycosidases. The results of these studies indicated that the mature gp55-116 is synthesized by the addition of both simple and complex N-linked sugars to a nonglycosylated precursor of estimated Mr 105,000. In a rapid processing step, the Mr 105,000 precursor is glycosylated to a protein of Mr 150,000 (gplS0) which contains only endoglycosidase H-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 24 publications
5
58
0
Order By: Relevance
“…The two cleavage products form a functional heterodimer (31,32). The different stages of gB processing are distinguishable through differential SDS/PAGE migration (31,32). We examined gB accumulation at 72 hpi in the presence of DMSO, PALA, and uridine and found that PALA treatment resulted in a decrease in the mature 116-kDa glycosylated form and an increase in the unglycosylated 105-kDa form (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two cleavage products form a functional heterodimer (31,32). The different stages of gB processing are distinguishable through differential SDS/PAGE migration (31,32). We examined gB accumulation at 72 hpi in the presence of DMSO, PALA, and uridine and found that PALA treatment resulted in a decrease in the mature 116-kDa glycosylated form and an increase in the unglycosylated 105-kDa form (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The gB protein goes through several posttranslational modifications. The nascent protein (∼105 kDa) is first glycosylated, giving rise to an ∼170-kDa product, before being transported to the Golgi, where it is cleaved to form the mature protein, which consists of two fragments, one of ∼116 kDa and the other 55 kDa (31,32). The two cleavage products form a functional heterodimer (31,32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, these studies highlight the possibility that antibodies to GDEs are more common than previously appreciated. This insight has implications for our understanding of the protective immune responses to the highly glycosylated proteins of other pathogens such as cytomegalovirus (Britt and Vugler, 1989), SARs-CoV, influenza, and West Nile virus (Vigerust and Shepherd, 2007). Until recently, vaccines were developed to epitopes that were primarily amino acids or carbohydrates, but not a combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…gB is a polyprotein of M r 160000 that is cleaved at position 460 (CL-cleavage site region aa 384-717) by a cellular endoprotease to produce the N-(M r 92000-116000) and C-(M r 52000-55000) terminal products [17]. Finally, the fully processed homodimeric disulfide-linked gp116-gp55 complex is assembled and can be detected on the surface of both infected cells and virions [18]. gB is encoded by ORF UL55 (2721nt), transcribed as an early-late unspliced transcript.…”
Section: Gc-i (Glycoprotein B; Gb)mentioning
confidence: 99%